Exploration of the role of mosques in community development: Malaysian experience - Bahari, Che Amnah; Shihabuddin, ASM (WorldConferences.net (Koperasi KOKUIS Kolej Universiti Islam Antarabangsa Selangor), 2016)
Community based organizations including faith-based organization are increasingly assuming greater roles in addressing social issues at local level all over the world. Mosques are institutions of critical social importance because they are at the same time a place for spiritual devotion and a center for community development. Malaysia is a leading Muslim country and its mosques are expected to exhibit the performance of comprehensive roles which mosques in other parts of the world can take as a model. In line with this expectation, the proposed study aims at exploring the roles of mosques at Malaysian locality in community engagement and development. The focus of the survey is to find out if the respondents attribute their consciousness of pressing social issues and their participation in community development activities to the lectures and speeches they listen to in the mosques. Qualitative and quantitative analysis of the information obtained from these sources will be performed to identify and categorize the role of the selected mosques. The overall outcome of the proposed study is expected to increase our understanding of the current community development role of Malaysian mosques and offer insight for policy initiatives towards broadening and deepening this role where necessary